Pharyngeal Residue Is Independently Associated With Mortality and Aspiration Events in Patients Undergoing Swallowing Assessment: A Retrospective Cohort Study - Yuki Chiko; Shizuma Omote; Ei Miyasaka (Journal of General and Family Medicine, 2026)
ABSTRACT Background The prognostic significance of pharyngeal residue during routine swallowing assessment remains unclear in older adults at regional hospitals. Methods We conducted a single‐center retrospective cohort study of 107 consecutive patients (median age 87 years) undergoing swallowing assessment at a regional hospital in Japan (January 2021–December 2024; follow‐up until June 2025). The primary outcome was all‐cause mortality, and the secondary outcome was aspiration events. Time‐to‐event analyses used Kaplan–Meier methods, multivariable Cox proportional hazards models, and Fine–Gray subdistribution hazard models to account for the competing risk of death. Results During a median follow‐up of 72 days (IQR 36–156), 72 deaths and 63 aspiration events occurred. Pharyngeal residue was independently associated with aspiration events (HR 3.26; 95% CI 1.70–6.26; p < 0.001) and all‐cause mortality (HR 2.65; 95% CI 1.38–5.10; p = 0.003). These findings were consistent in sensitivity analyses excluding antipsychotic use and in Fine–Gray competing risks analysis (SHR 2.76; 95% CI 1.51–5.04; p = 0.001). Dementia was also independently associated with mortality (HR 1.83; 95% CI 1.02–3.29; p = 0.044). Conclusions Pharyngeal residue was independently associated with all‐cause mortality and aspiration events, supporting its utility as a simple prognostic marker for risk stratification in older adults with suspected dysphagia.